The anatomy of the hindlimb of Theropithecus brumpti (Cercopithecidae, Papionini): Morphofunctional implications. Issue 178 (May 2023) - Pallas, Laurent; Daver, Guillaume; Merceron, Gildas; Boisserie, Jean-Renaud
Abstract: Theropithecus brumpti is a primate known from numerous craniodental specimens in the Plio-Pleistocene Shungura Formation (Lower Omo Valley, Ethiopia), but the anatomy of its hindlimb is documented only by a few associated and mostly incomplete postcranial specimens. The adaptations of T. brumpti are still debated, with its substrate preferences and its use of squatting postures recently discussed based on anatomical differences when compared with its extant representative, Theropithecus gelada . Here, we describe an associated femur and tibia (L 869-1 and L 869-2) of a presumed T. brumpti male and a partial foot (L 865-1r and L 865-1t) of a male T. brumpti, dated to ca. 2.6 Ma and ca. 2.32 Ma respectively. Based on univariate and bivariate morphometric analyses, we provide new data on the morphological correlates of substrate preferences and postural behaviors of this fossil species. Our results are in agreement with previous analyses and present T. brumpti as a predominantly terrestrial primate. We demonstrate the presence of osteological correlates associated with the use of squatting behaviors in T. brumpti but also point to significant anatomical differences between this paleontological species and T. gelada . These differences blur the functional value of characters previously identified as diagnostic of T. gelada and its postural behavior. We further document the postcranial distinctiveness of the Theropithecus clade in relation to the Papio clade. This study thus provides new insights into the postcranial anatomy and paleoecology of an abundant fossil primate from the Plio-Pleistocene of eastern Africa.